Conceptualizing Accessibility for English Language Proficiency Assessments. Issue 1 (4th April 2016) - Guzman‐Orth, Danielle; Laitusis, Cara; Thurlow, Martha; Christensen, Laurene
Abstract: This paper is the second in a series from Educational Testing Service (ETS) that conceptualizes next‐generation English language proficiency (ELP) assessment systems for K‐12 English learners (ELs) in the United States. The first paper articulated a high‐level conceptualization of next‐generation ELP assessment systems (Hauck, Wolf, & Mislevy, 2016), the third paper addressed issues related to summative ELP assessments that emerged from the presentations and discussions at the English Language Proficiency Assessment Research working meeting (Wolf, Guzman‐Orth, & Hauck, 2016), and the fourth paper focused on a key concern within such systems—the initial identification and classification of ELs (Lopez, Pooler, & Linquanti, 2016). The goal of this paper is to address accessibility issues in the context of ELP assessments and to discuss critical considerations to improve the accessibility of ELP assessments for ELs and ELs with disabilities. Although accessibility for ELs and ELs with disabilities who are taking content assessments is also important, a discussion about content assessments is beyond the scope of the paper at this time. In this paper, we discuss challenges and areas of possible directions to pursue for ongoing and future ELP assessment development, policy implications, and research considerations to improve the ELP testing experience for all users. Abstract : Report Number: ETS RR‐16–07